2011
DOI: 10.1002/eji.201141879
|View full text |Cite
|
Sign up to set email alerts
|

HMGB1 blockade attenuates experimental autoimmune myocarditis and suppresses Th17‐cell expansion

Abstract: High-mobility group box 1 (HMGB1), a non-histone nuclear protein, has been implicated in cardiovascular diseases. Dilated cardiomyopathy (DCM), one of the leading causes of heart failure, is often caused by coxsackievirus B3-triggered myocarditis and promoted by the post-infectious autoimmune process. Th17 cells, a novel CD4 1 T subset, may be important in the pathogenesis of autoimmune myocarditis. In the present study, we attempted to block HMGB1 function with a monoclonal antibody specific for HMGB1 B box a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
63
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 55 publications
6
63
0
Order By: Relevance
“…HMGB1 can aggravate the myocardial injury by promoting the amplification of the number of Th17 cells in experimental myocarditis [14]. Specific HMGB1 monoclonal antibodies that block the Th17 cells in local myocardial tissues can reduce the injuries of cardiomyopathy [15]. In consistent with the previous studies, the present study found that serum HMGB1 levels were significantly higher in patients with heart failure.…”
supporting
confidence: 89%
“…HMGB1 can aggravate the myocardial injury by promoting the amplification of the number of Th17 cells in experimental myocarditis [14]. Specific HMGB1 monoclonal antibodies that block the Th17 cells in local myocardial tissues can reduce the injuries of cardiomyopathy [15]. In consistent with the previous studies, the present study found that serum HMGB1 levels were significantly higher in patients with heart failure.…”
supporting
confidence: 89%
“…HMGB1 is a positive regulator of Th17 cells and Th1 cells, as reported previously: Shi et al found that HMGB1 can increase the differentiation of Th17 cells in vitro through the elevation of RORgt mRNA expression [41]. Besides, inhibition of HMGB1 expression has been correlated with a reduced number of Th17 cells in heart tissue as well as with attenuated experimental autoimmune myocarditis [42]. HMGB1 causes the maturation of dendritic cells by increasing the expression of surface markers and stimulating the differentiation of T cells to the Th1 phenotype [43,44].…”
Section: Discussionmentioning
confidence: 64%
“…5A). HMGB-1 was reported to be involved in Th17 development in an experimental autoimmune encephalomyelitis model (28) and to play important roles in alkalineinduced corneal neovascularization through TLR4 (29). We observed that HMGB-1 also upregulated IL-17 secretion from gdT cells in collaboration with IL-1b (Fig.…”
Section: Hmgb-1 As An Inducer Of Il-1b From Macrophages and Il-17 Fromentioning
confidence: 58%